The impacts of the 1965 voting rights act on African American Franchise and its current issues = Ảnh hưởng của luật bầu cử 1965 đối với quyền bầu cử của người Mỹ gốc Phi và những vấn đề hiện nay - Doan, Phuong Thuy (2021)
As one of the most powerful and influential countries in the world, the United States of America has always inspired many researchers to carry out studies on many aspects of its social life, such as politics, education and race relations. The country with great emphasis on democracy and equality has been questioned on the realization of those values. On the way to gain equal voting rights for all, which is considered the symbol of American democracy and idea of equality, discriminated groups of Americans have experienced many struggles. Of all the groups suffering from discrimination in voting, black Americans has been standing out for their long and even fierce history of concerted efforts to protect their voting right – a fundamental civil right. It is a major shortcoming not to mention The 1965 Voting Rights Act in the research on African American struggle for voting right. It is not until the Act that the group’s voting right is really protected from discrimination despite being legally claimed long before the enactment of the Act. The Act has played such an important role in the guaranty of black voting that nearly half the century later, its changes still stir up heating debates. Inspired by the situation, the researcher investigates African American voting in association with The 1965 Voting Rights Act. After carrying out the research, the researcher find out that thanks to its improved points in comparison with Civil Rights Acts, Voting Rights Act has greatly contributed to the improvement of black American voting, which is represented by the dramatic increase in black voter turnout, registration rates and elected legislators as well as to better relation between blacks and whites. However, the blacks are now underrepresented for the whites’ remaining unwillingness to vote for blacks. Therefore, blacks are vulnerable to discriminatory voting laws because of the Supreme Court’s decision to invalidate the coverage formula of the Act’s Section 4.